Development of Continuous Flow Systems to Access Secondary Amines Through Previously Incompatible Biocatalytic Cascades. (19th May 2021) - Mattey, Ashley P.; Ford, Grayson J.; Citoler, Joan; Baldwin, Christopher; Marshall, James R.; Palmer, Ryan B.; Thompson, Matthew; Turner, Nicholas J.; Cosgrove, Sebastian C.; Flitsch, Sabine L.
Abstract: A key aim of biocatalysis is to mimic the ability of eukaryotic cells to carry out multistep cascades in a controlled and selective way. As biocatalytic cascades get more complex, reactions become unattainable under typical batch conditions. Here a number of continuous flow systems were used to overcome batch incompatibility, thus allowing for successful biocatalytic cascades. As proof‐of‐principle, reactive carbonyl intermediates were generated in situ using alcohol oxidases, then passed directly to a series of packed‐bed modules containing different aminating biocatalysts which accordingly produced a range of structurally distinct amines. The method was expanded to employ a batch incompatible sequential amination cascade via an oxidase/transaminase/imine reductase sequence, introducing different amine reagents at each step without cross‐reactivity. The combined approaches allowed for the biocatalytic synthesis of the natural product 4O‐methylnorbelladine. Abstract : The use of continuous flow reactors enabled previously inaccessible enzyme combinations in multi‐enzyme cascade reactions. This included the combination of oxidases with aminating biocatalysts (transaminase/reductive aminase) and was extended to the continuous in situ biocatalytic generation of amino donors for the reductive aminase.